Effects of assimilate enhancement on grain filling and carbohydrate and nitrogen partitioning in maize. - MAGALHAES, P. C. (1984)
Source-sink relationhips is a controversial topic. Some workers assert that grain yield in corn is limited by availability of assimilate during the grain filling period. Others have reported the sink size as the limiting factor. In this research, I studied the effects of assimilate availabilibty on kernel growth rate and final weight by investigating the effects of altered source/sink ratios on soluble sugars, starch and nitrogen content in plant parts of maize. Special attention was given to plant's compensatory response such as soluble carbohydrates and nitrogen redistribution to the grain. Two genotypes: M14 x W64A and Pionner-brand '3780', were grown in field plots at St. Paul, Mn in 1982. The treatment were arranged in a split plot manner in a randomized complete block design of four replicates. The alterations of source/sink ratio consisted of partial kernel removal (removing the tip half of the ear), and thinning by a 50% plant population reduction imposed before and after the onset of linear growth (6 days and 24 days after mid-silking, respectively). M14 x W64A responded to early thinning, as indicated by an extended grain filling period, increased starch content of the kernels and greater final kernel weight. However, kernel growth rate, number of kernels per ear and kernel soluble sugars content were not affected. Thinning and partial kernel removel on both dates increased internode dry weight and soluble sugar content. Kernels removal early enhanced the nitrogen content in the internodes and (...)